2007
DOI: 10.1016/j.ijheh.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence of effects of environmental chemicals on the endocrine system in children

Abstract: Pollutant chemicals that are widespread in the environment can affect endocrine function in laboratory experiments and in wildlife. Although human beings are commonly exposed to such pollutant chemicals, the exposures are generally low and clear effects on endocrine function from such exposures have been difficult to demonstrate. Human data including both exposure to the chemical agent and the endocrine outcome are reviewed here, including age at weaning, age at puberty, anogenital distance, and sex ratio at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…It had been suspected that the decline in the age of menarche over the years was due to improved standard of living. However recent studies have implicated endocrine disrupting chemicals in the environment as being responsible for this trend [19,[21][22][23] . Girls with high levels of lead in their blood had delayed menarche in US while exposure to dichlorodiphenyl trichloroethane (DDT), has been reported to decrease the age of menarche [35][36] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been suspected that the decline in the age of menarche over the years was due to improved standard of living. However recent studies have implicated endocrine disrupting chemicals in the environment as being responsible for this trend [19,[21][22][23] . Girls with high levels of lead in their blood had delayed menarche in US while exposure to dichlorodiphenyl trichloroethane (DDT), has been reported to decrease the age of menarche [35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…In these girls significantly high levels of phthalates and their major metabolites were identified in 68% of patients with premature thelarche, while less than 1% of controls had high levels of these chemicals [20] . The evidence of environmental chemicals as chemical disrupting agents has been reported [21] , while the effect of estrogenic agents on pubertal growth and maturation of the reproductive system has been reported in rhesus monkeys [22] . Endocrine-disrupting chemicals from the environment are now recognized as one of the causes of reduced age of menarche in girls migrating to industrialized countries [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the toxic effects of PHAHs may not be evident even from high level exposure, the local residents might have already been suffering from (or subjected to) certain subclinical effects from exposure to these compounds. Adverse health effects (such as carcinogenicity, developmental defects, immunotoxicity, neurotoxicity, and reproductive toxicity) induced by PHAHs in the three study subfamilies have been reported in humans (Safe,1994;Rogan and Ragan, 2003) and other species (US ATSDR, 2004;UNEP, 2006;POPRC, 2007a,b). Therefore, further research is needed into the long-term health impacts of chronic exposure to PHAHs for those Chinese residents who spend much of their time around an e-waste disassembly site.…”
Section: Health Implicationsmentioning
confidence: 96%
“…Although the toxic effects of POP exposure may not be evident at birth even at high levels, its subclinical toxicity in the fetus is always a possibility. Toxicities caused by transplacental passage to PCBs have been reported in humans (Jacobson et al, 1984;Rogan and Ragan, 2003) and other species (Allen et al, 1974;Haake et al, 1987). Therefore, further research is needed into the health impacts of prenatal exposure to POPs in China and other countries.…”
Section: Health Implicationsmentioning
confidence: 99%